The bittersweet effects of COVID-19 on mental health: Results of an online survey among a sample of the Dutch population five weeks after relaxation of lockdown restrictions - Gijzen, Mandy; Shields-Zeeman, Laura; Kleinjan, Marloes; Kroon, Hans; van der Roest, Henriëtte; Bolier, Linda; Smit, Filip; de Beurs, Derek (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Previous research shows that crises can have both negative and positive mental health effects on the population. The current study explored these effects in the context of the COVID-19 pandemic after relaxation of governmental measures. An online survey was administered among a representative sample of the Dutch population (n = 1519) in June 2020, ten weeks after the peak of COVID-19 had passed, and five weeks after restrictions were relaxed. Participants were asked about mental health, adverse events during COVID-19, and about any positive effects of the pandemic. Most participants (80%, n = 1207) reported no change in mental health since the COVID-19 pandemic. This was also the case among respondents who had experienced an adverse event. Protective factors of mental health were being male and high levels of positive mental well-being. Risk factors were emotional loneliness and the experience of adverse life events. Social loneliness was positively associated with stable mental health, stressing the importance of meaningful relationships. Note that 58% of participants reported positive effects of the pandemic, the most common of which were rest, working from home, and feeling more socially connected. In summary, 10 weeks after the start of the crisis, and 5 weeks after relaxation of the restrictions, most people remained stable during the crisis, and were even able to report positive effects.
Keywords: COVID-19; Lockdown; Mental health; Positive effects; Stability; Public Health, Environmental and Occupational Health; Health, Toxicology and Mutagenesis; SDG 3 - Good Health and Well-being